2017
DOI: 10.1007/s11356-017-1045-4
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and biological monitoring of exposures to VOCs in a petrochemical complex in Iran

Abstract: Exposure to volatile organic compounds (VOCs) can cause cancers in human. This study aimed to measure the concentration of four VOCs including benzene, styrene, ethylbenzene, and phenol in ambient air of a petrochemical complex in Iran. Also, their urinary metabolites including phenol, mandelic acid (MA), and phenylglyoxylic acid (PGA) in the workers were monitored. Urine samples were collected before and after the 8-h workshift according to the NIOSH methods. They were analyzed by a gas chromatograph coupled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…At the manufacturing process, styrene is combined with other chemicals at high temperature, which induces the release of styrene vapors into the environment. Several studies have shown that exposure to these fumes can have negative health effects [ 10 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…At the manufacturing process, styrene is combined with other chemicals at high temperature, which induces the release of styrene vapors into the environment. Several studies have shown that exposure to these fumes can have negative health effects [ 10 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Volatile organic chemicals (VOCs) are also the major pollutants coming from a petrochemical plant and are carcinogenic in nature. A study conducted by Hajizadeh et al (2018) in a petrochemical plant in Iran found that when workers are exposed to VOCs such as phenol, ethylbenzene, benzene, styrene, and phenol in ambient air, they are likely to suffer from cancer. A similar study was conducted Wang et al (2015) in China on PAH exposure of workers employed in a petrochemical plant.…”
Section: Ramifications Of Petrochemical Industry Wastewaters On Environmentmentioning
confidence: 99%
“…The special effects of these compounds include their role in reducing stratospheric ozone, global warming, and toxic and carcinogenic effects on human health [ 16 , 17 ]. So far, many studies have been performed to measure VOCs in the air or their urinary metabolites [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%